Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
x = 3, y = - 9
Step-by-step explanation:
5x + 5y = - 30...... (1)
2x - y = 15
-y = 15 - 2x
y = 2x - 15..... (2)
From equations (1) & (2)
5x + 5(2x - 15) = - 30
5x + 10x - 75 = - 30
15x = 75 - 30
15x = 45
x = 45/15
x = 3
Plug x = 3 in equation (2)
y = 2*3 - 15
y = 6 - 15
y = - 9
Therefore,
x = 3, y = - 9
or
(x, y) = (3, - 9)
5x + 5y = -30
Divide through by 5
X + Y = -6
Multiplying the equation by 2 and the equation 2x - y = 15 by 1 in order to get rid of x
2x + 2y = -12
2x - y = -15
Subtracting both equations
3y=3
y=1
Substituting y = 1 to get x in any equation
Using 2x - y = -15
2x - 1 = -15
2x =-15 + 1
2x = -14
x = -14/2
x = -7
Divide through by 5
X + Y = -6
Multiplying the equation by 2 and the equation 2x - y = 15 by 1 in order to get rid of x
2x + 2y = -12
2x - y = -15
Subtracting both equations
3y=3
y=1
Substituting y = 1 to get x in any equation
Using 2x - y = -15
2x - 1 = -15
2x =-15 + 1
2x = -14
x = -14/2
x = -7
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.